Factors that Drive Employee Engagement in Organizations: A Review - Tewari , Isha (International Journal of Psychosocial Rehabilitation, 2020)
In the current time of globalization and increased competition in the global business environment, a management approach like employee engagement has started attaining huge significance. However, it is seen that many organizations still fail to reap the desired results of employee engagement due to a lack of awareness about the affecting factors. As engaged employees are fully aware of their job responsibility, they align their individual goals with the organizational goals with optimum commitment towards the welfare of the organization. This article reviews the current knowledge of significant factors and workplace practices that can drive employee engagement in organizations. It discusses some key predictors of employee engagement as suggested by the other researchers, such as career development, employee empowerment, interpersonal relationships, communication, leadership, organizational culture, job design, compensation system, performance management, and individual factors like extraversion, conscientiousness, and positive affectivity that can help companies in increasing organizational effectiveness by keeping their employees engaged. Secondary data from articles in various management journals, books, websites, and periodicals have been reviewed for this purpose. The article shows that a single factor cannot contribute to employee engagement alone; rather, a combination of multiple factors helps it to develop. This review will be of value to any organization seeking knowledge on the approach to employee engagement for improving productivity at the workplace, reducing staff turnover, and increasing profits.